Is the Severity of the Clinical Expression of Anorexia Nervosa Influenced by an Anxiety, Depressive, or Obsessive-Compulsive Comorbidity Over a Lifetime? - Riquin, Elise; Raynal, Agathe; Mattar, Lama; Lalanne, Christophe; Hirot, France; Huas, Caroline; Duclos, Jeanne; , EVHAN group; Berthoz, Sylvie; Godart, Nathalie; Godart, Nathalie; Berthoz, Sylvie; et al. (Frontiers in Psychiatry, 2021)
Purpose : The relationship between anxiety or depressive comorbidities, their chronology of onset and the severity of anorexia nervosa (AN) is not well studied. We hypothesize that the existence of a comorbidity, particularly before the AN, is associated with greater severity of AN. Methods: One hundred seventy-seven subjects were assessed. The prevalence of major depressive disorder (MDD), obsessive-compulsive disorder (OCD), generalized anxiety disorder (GAD) and social phobia (SP) and their chronology of onset were studied. The assessment criteria of AN severity were: the overall clinical condition, body mass index (BMI) on admission, lowest BMI, intensity of the eating symptoms, age at the onset of AN, illness duration, number of hospitalizations and quality of life. Results: Patients with AN had the greatest clinical severity when they had a comorbid disorder over their lifetime such as MDD, GAD or SP. These comorbidities along with OCD were associated with a higher level of eating symptoms and a more altered quality of life. A profile of maximum severity was associated with a higher prevalence of MDD and GAD. Concerning the chronology of onset, the age at the start of AN was later in cases of MDD or GAD prior to AN. Conclusion : There seems to be an association between severity of AN and MDD and GAD. The chronology of onset of the comorbidity did not seem to be associated with the severity.